Efektivitas E-Modul Hidrokarbon Berbasis Guided Discovery Learning terhadap Hasil Belajar Peserta Didik Kelas XI Di SMAN 13 Padang - Ameliana Fitriyanti; Yerimadesi Yerimadesi (Universitas Batanghari Jambi, 2023)
In the hydrocarbon material, there is a lot of conceptual, factual, and procedural knowledge that must be managed by students. One component of learning success is determined by the quality of teaching materials provided to students. Therefore, teaching materials are used to comply with the requirement of students in understanding hydrocarbon materials in the form of a hydrocarbon e-module based on guided discovery learning that has been valid and practical so that it can improve student learning outcomes. The purpose of this study was to determine the effectivity of the e-module used on student learning outcomes at SMAN 13 Padang. This research is quasi-experimental research (Quast Experiment Research) using a nonequivalent control group design. The population is class XI MIPA SMAN 13 Padang in the academic year 2022/2023. The sample selection was done by random sampling technique, by choosing class XI MIPA 2 as the experimental class and class XI MIPA 4 as the control class. The instrument used in this study was a multiple-choice test consisting of 25 questions and 5 valid, reliable, and discriminatory answer choices, and a difficulty index with good criteria. The effectivity level of the e-module was analyzed from the n-gain test value. The results obtained n-gain in the experimental class 0.6 while in the control class 0.55 with a medium category. So that the hydrocarbon e-module based on guided discovery learning is effectively used to improve student learning outcomes.